2019
DOI: 10.1101/554303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral immunization with a probiotic cholera vaccine induces broad protective immunity againstVibrio choleraecolonization and disease in mice

Abstract: 23Oral cholera vaccines (OCVs) are being increasingly employed, but current killed formulations 24 generally require multiple doses and lack efficacy in young children. We recently developed a 25 new live-attenuated OCV candidate (HaitiV) derived from a Vibrio cholerae strain isolated during 26 the 2010 Haiti cholera epidemic. HaitiV exhibited an unexpected probiotic-like activity in infant 27 rabbits, preventing intestinal colonization and disease by wild-type V. cholerae before the onset 28 of adaptive immun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…An important caveat underlying our findings is that GF mice lack commensal gut microbes and could have altered immune responses to immunization, especially considering recent studies that have highlighted how V. cholerae-microbiota interactions can influence colonization, disease, and development of anti-V. cholerae immunity [48][49][50][51][52] . However, the strong association of VAT induction with protection and superior efficacy of live over inactivated vaccine strains in this model, and our similar findings of OCV function in mice with transiently disrupted microbiomes reinforces the idea that the GF mouse live OCV model holds substantial translational promise 36,37 .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…An important caveat underlying our findings is that GF mice lack commensal gut microbes and could have altered immune responses to immunization, especially considering recent studies that have highlighted how V. cholerae-microbiota interactions can influence colonization, disease, and development of anti-V. cholerae immunity [48][49][50][51][52] . However, the strong association of VAT induction with protection and superior efficacy of live over inactivated vaccine strains in this model, and our similar findings of OCV function in mice with transiently disrupted microbiomes reinforces the idea that the GF mouse live OCV model holds substantial translational promise 36,37 .…”
Section: Discussionsupporting
confidence: 75%
“…Pups in all three live vaccine groups were significantly protected from both death and diarrhea caused by challenge with either serotype compared with pups in the FKV group that exhibited similar kinetics of mortality as pups of unvaccinated dams, indicating that the presence of VATs (i.e. seroconversion) is tightly correlated with protection in this model ( Figure 3BC) 36,37 . However, the protective efficacy of the three vaccine serotypes differed depending on the serotype of the challenge strain.…”
Section: Vaccine Serotype Influences Vaccine Protective Efficacymentioning
confidence: 88%
See 2 more Smart Citations
“…It has been shown that subcutaneous and oral immunization with SIP induces a protective humoral and cellular immune response [ 18 , 19 ]. In the context of oral immunization strategies, the route of administration would be adequate for the generation of mucosal immunity, which has already been proven to generate protection against diseases such as cholera and polio [ 20 , 21 ]. An oral vaccine might be advantageous for the distribution and administration of GBS vaccines, which could improve the uptake of antigen vaccination and overall public health.…”
Section: Introductionmentioning
confidence: 99%